Technical, Strategic, and Cultural Bottlenecks of Born-Global-Digital Firms - Fraccastoro, Sara; Ojala, Arto; Gabrielsson, Mika (University of Hawai'i at Manoa, 2023)
A born-global-digital firm belongs to the group of firms that apply and develop digital technologies to achieve early internationalization. However, there might be different types of bottlenecks related to foreign market entries and the development of digital services affecting those markets that limit such firms’ global activities. In this work, we divide these bottlenecks into technical, strategic, and cultural forms. This multi-case study examines the impact of those bottlenecks and how that might be overcome. We provide practical and theoretical alternatives to bypass the impediments created by the bottlenecks.
Keywords: Born-global; digital; technical; strategic; cultural; bottlenecks; fi=Kansainvälinen liiketoiminta|en=International Business|